(untitled) (Praxis Educativa, 2024)
The article presents teaching trends in terms of preferences for teaching modalities for their subjects (face to face, blended or virtual) after having gone through the COVID-19 pandemic, during which it was forced to sustain teaching virtually. An exploratory, descriptive study was carried out, with a non-experimental design, supported by a mixed approach, so that data of a qualitative and quantitative nature were worked with. 169 Argentine university professors participated and responded to a questionnaire in which they were asked about their preferred subject teaching modality, as well as the reasons that justify said choice. The results show a majority choice of blended learning, understood by teachers as a modality that meets the needs of the student, who allows, by combining face-to-face and virtuality, to access certain advantages over pure pedagogical options and ensure higher levels of inclusion.